Analisis Pertumbuhan Ekonomi Pasca Covid-19 Terhadap Nilai Inflasi yang ada Di Indonesia: Analisis Pertumbuhan Ekonomi Pasca Covid-19 Terhadap Nilai Inflasi yang ada Di Indonesia - Ambarwati, Silvy; Andika, Cahya; Putri Achira, Shabrida; Andina, Aulia; Panorama, Maya (UIR Press, 2023)
This research was conducted to determine the impact of theCovid-19 pandemic virus in Indonesia on economic growth andthe rate of inflation. The Covid-19 pandemic virus is a deadlyvirus which is becoming a global issue and problem for theentire world community. This virus causes so many problems in various aspects, including the economy. The results of thisresearch conclude that the Covid-19 virus is linked to the rate ofinflation and economic growth in Indonesia. Because it causes a decline in various areas of economic activity, includingunemployment rates, supply and demand levels, and continuousprice increases which disrupt the rate of economic growth in Indonesia.